1990
DOI: 10.1128/aem.56.12.3822-3829.1990
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the bacteriological activity associated with granular activated carbon treatment of drinking water

Abstract: Bacteriological analyses were performed on the effluent from a conventional water treatment pilot plant in which granular activated carbon (GAC) had been used as the final process to assess the impact of GAC on the microbial quality of the water produced. Samples were collected twice weekly for 160 days from the effluents of six GAC columns, each of which used one of four different empty-bed contact times (7.5, 15, 30, and 60 min). The samples were analyzed for heterotrophic plate counts and total coliforms. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 22 publications
1
33
1
Order By: Relevance
“…In spite of ozone disinfecting, the BAC effluent had higher bacterial counts than the one from ozonation, probably because of the release of excess biofilm (Stewart et al, 1990). Our first attempt to characterize the microbial composition of the effluent showed that, among the analyzed microrganisms, the beta class is the most represented in the BAC effluent, while the alpha-proteobacteria seem the most sensitive to ozone effect.…”
Section: Discussionmentioning
confidence: 92%
“…In spite of ozone disinfecting, the BAC effluent had higher bacterial counts than the one from ozonation, probably because of the release of excess biofilm (Stewart et al, 1990). Our first attempt to characterize the microbial composition of the effluent showed that, among the analyzed microrganisms, the beta class is the most represented in the BAC effluent, while the alpha-proteobacteria seem the most sensitive to ozone effect.…”
Section: Discussionmentioning
confidence: 92%
“…As observed by Morton and O l i x r (199.C), most of these proteins are induced at the beginning (from 0 to 3 h) of stress conditions, or assuming that bacterial aggregates ma!-contribute to the heterotrophic plate count. Each of these aggregates can contain a high and variable number of cells (Hicks and Rowbury 1986;Van Loosdrecht 1988;Stewart et a/. 1990).…”
Section: Observation Of Aggregatesmentioning
confidence: 99%
“…Carbon particles provide attractive sites for the attachment of bacteria. The number of bacteria attached to GAC particles in the effluent of a water treatment pilot plant was assessed in a study conducted by Stewart et al (1990). With scanning electron microscopy, it was found that 85% of the GAC particles harbored fewer than 50 bacteria and 8% harbored anywhere from hundreds to thousands of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…LeChevallier (1984LeChevallier ( , 1988b found that bacteria attached to GAC particles were more resistant to chlorine disinfection than free-swimming bacteria. Stewart et al (1990) reported that neither free chlorine nor combined chlorine successfully inactivated bacteria attached to GAC particles.…”
Section: Introductionmentioning
confidence: 99%